Efferocytosis and Lung Disease - McCubbrey, Alexandra L. (American College of Chest Physicians, 2013)
In healthy individuals, billions of cells die by apoptosis each day. Clearance of these apoptotic cells, termed “efferocytosis,” must be efficient to prevent secondary necrosis and the release of proinflammatory cell contents that disrupt tissue homeostasis and potentially foster autoimmunity. During inflammation, most apoptotic cells are cleared by macrophages; the efferocytic process actively induces a macrophage phenotype that favors tissue repair and suppression of inflammation. Several chronic lung diseases, particularly airways diseases such as chronic obstructive lung disease, asthma, and cystic fibrosis, are characterized by an increased lung burden of uningested apoptotic cells. Alveolar macrophages from individuals with these chronic airways diseases have decreased efferocytosis relative to alveolar macrophages from healthy subjects. These two findings have led to the hypothesis that impaired apoptotic cell clearance may contribute causally to sustained lung inflammation and that therapies to enhance efferocytosis might be beneficial. This review of the English-language scientific literature (2006 to mid-2012) explains how such existing therapies as corticosteroids, statins, and macrolides may act in part by augmenting apoptotic cell clearance. However, efferocytosis can also impede host defenses against lung infection. Thus, determining whether novel therapies to augment efferocytosis should be developed and in whom they should be used lies at the heart of efforts to differentiate specific phenotypes within complex chronic lung diseases to provide appropriately personalized therapies.